Investigation of the motor skills assessments of typically developing preschool children in China - H. Q. Song; P. W. C. Lau; J. J. Wang (BMC, 2022)
Abstract Background The assessment of preschoolers' motor skills is essential to know young children's motor development and evaluate the intervention effects of promotion in children's sports activities. The purpose of this study was to review the motor skills assessment tools in Chinese pre-school-aged children, compare them in the international context, and provide guidelines to find appropriate motor skill assessment tools for developing children in China. Methods A comprehensive literature search was carried out using the WANFAGN, CNKI, VIP, ERIC, EMBASE, MEDLINE, and SPORT Discus databases. Relevant articles published between January 2000 and May 2020 were retrieved. Studies that described the discriminative and evaluative measures of motor skills among the population aged 3-6 years in China were included. Results A total of 17 studies were included in this study describing seven tools, including four self-developed tools and three international tools used in China. TGMD-2 appeared in a large proportion of the studies. The international tools used in China were incomplete in terms of translation, verification of reliability and validity, item selection, and implementation. Regarding the self-constructed tools, the CDCC was the most utilized self-developed tool, but it was mainly applied in intellectual development assessment. By comparing Chinese self-constructed and international tools, the construction of the CDCC and the Gross Motor Development Assessment Scale contained relatively complete development steps. However, the test content, validity and reliability, implementation instruction, and generalizability of self-constructed tools are still lacking. Conclusions Both international and self-developed motor skills assessment tools have been rarely applied in China. Available tools lack enough validation and appropriate adjustments. Cultural differences in motor development between Chinese and Western populations should be considered when constructing a Chinese localized motor skill assessment tool.